Diversity of Babesia spp. in cervid ungulates based on the 18S rDNA and cytochrome c oxidase subunit I phylogenies - Hrazdilová, Kristýna; Rybářová, Markéta; Široký, Pavel; Votýpka, Jan; Zintl, Annetta; Burgess, Hilary; Steinbauer, Vladimír; Žákovčík, Vladimír; Modrý, David (Infection, genetics and evolution, 2020)
Free ranging ungulates, represented in Europe mostly by several deer species, are important hosts for ticks and reservoirs of tick-borne infections. A number of studies have focused on the prevalence of tick borne pathogens in deer chiefly with the aim to determine their potential role as reservoir hosts for important human and livestock pathogens. However, genetic similarity of Babesia spp. forming a group commonly termed as a clade VI that accommodates the deer piroplasms, complicates this task and has led to the description of a bewildering array of poorly characterised strains. This study aims to resolve this issue by using two independent genetic loci, nuclear 18S rRNA and mitochondrial cytochrome c oxidase subunit I genes, used in parallel to identify Babesia isolates in free-ranging red, sika, and roe deer in two areas of their co-occurrence in the Czech Republic. The COX1 loci, in contrast to 18S rRNA gene, shows a clear difference between interspecific and intraspecific variation at the nucleotide level. The findings confirm B. divergens, Babesia sp. EU1 and B. capreoli in studied deer species as well as common presence of another unnamed species that matches a taxon previously referred to as Babesia sp. or Babesia cf. odocoilei or Babesia CH1 group in several other sites throughout Europe. The invasive sika deers enter the life cycle of at least three piroplasmid species detected in native deer fauna. The presence of B. divergens in both sika and red deer in an area where bovine babesiosis is apparently absent raises important questions regarding the epidemiology, host specificity and taxonomic status of the parasite.
Keywords: molekulární evoluce; Babesiosis; fylogeneze; protozoální DNA; cyklooxygenasa 1; DNA, Ribosomal; Male; ribozomální DNA; protozoální proteiny; RNA ribozomální 18S; Piroplasmids; Animals; DNA, Protozoan; Protozoan Proteins; Cyclooxygenase 1; Deer; Czech Republic; vysoká zvěř; Sequence Analysis, DNA; zvířata; 18S rDNA; mužské pohlaví; RNA, Ribosomal, 18S; Phylogeny; babezióza; Česká republika; ženské pohlaví; sekvenční analýza DNA; Babesia; COX1; Female; Evolution, Molecular